Changes of adolescent sleep patterns during the COVID-19 pandemic - Mariana Otero Xavier; Jessica Mayumi Maruyama; Iná S. Santos; Luciana Tovo-Rodrigues; Aluísio J. D. Barros; Alicia Matijasevich (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE The COVID-19 pandemic has raised numerous concerns regarding its effects on individuals' health and lifestyle. We aim to analyze potential changes in adolescent sleep patterns from before and during the pandemic and identify specific predictors of changes. METHODS A subgroup of adolescents from a population-based birth cohort from Pelotas, Brazil, was assessed pre-pandemic (T1, November-2019 to March-2020) and peri-pandemic (T2, August-2021 to December-2021) in in-person interviews (n = 1,949). Sleep parameters, including sleep duration and latency time on workdays and free days, as well as social jetlag (SJL), were assessed using the Munich ChronoType Questionnaire (MCTQ). Socio-demographic, pre-pandemic, and pandemic-related predictors were analyzed. Changes in sleep parameters from T1 to T2 were estimated by multivariate latent change score modeling. RESULTS The latent change factor shows a significant mean increase in workday sleep duration (M = 0.334, p < 0.001), workday sleep latency (M = 0.029, p = 0.002), and free day sleep latency (M = 0.021, p = 0.034), and a decreased in SJL (M = −0.758, p < 0.001) during the pandemic. Female adolescents presented higher increases in workday sleep duration. Adolescents who adopted a stricter social distancing level during the pandemic presented greater increases in workday sleep duration and smaller reductions in SJL. Self-evaluated insomnia during the pandemic predicted lower increases in workday and free day sleep duration and higher increases in workday and free day sleep latency. CONCLUSION The COVID-19 outbreak brought certain advantages regarding increased sleep duration and reduced SJL. However, the observed increase in sleep latency and the influence of self-reported insomnia could be related to psychological distress inherent to the pandemic.